2012
DOI: 10.1128/aac.06283-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Predictors of Clinical Potency for Hepatitis C Virus Nonnucleoside Polymerase and Protease Inhibitors

Abstract: This analysis was conducted to determine whether the hepatitis C virus (HCV) viral kinetics (VK) model can predict viral load (VL) decreases for nonnucleoside polymerase inhibitors (NNPolIs) and protease inhibitors (PIs) after 3-day monotherapy studies of patients infected with genotype 1 chronic HCV. This analysis includes data for 8 NNPolIs and 14 PIs, including VL decreases from 3-day monotherapy, total plasma trough concentrations on day 3 (C min ), replicon data (50% effective concentration [EC 50 ] and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 31 publications
3
44
1
Order By: Relevance
“…9,13,19 The relationship between drug concentration and antiviral effectiveness in blocking viral production can be described by an E-max model (Equation 3) εfalse(tfalse)=EmaxCfalse(tfalse)nEC50n+Cfalse(tfalse)n where C(t) is the drug concentration at time t ; EC 50 is the drug concentration needed to achieve an effectiveness of 50% of the maximum effect, E max ; and n is the Hill coefficient, a constant that determines the steepness of the drug concentration–effect curve. 22,31 Because drug concentrations are sometimes unavailable, empirical models have also been proposed to describe the patterns of change in drug effectiveness over time, 32,33 such as an exponential model for drugs whose concentrations decay or build up over time (Equation 4) εfalse(tfalse)=ε1+false(ε2ε1false)false(1ekεtfalse) where the treatment effectiveness starts from an initial level, ε 1 , changes to a final level, ε 2 , with k ε representing the rate of change of effectiveness. Therefore, if ε 2 is < ε 1 the model can mimic the effect of a decrease in drug effectiveness over time, as observed for example near the end of the dosing interval with weekly PEG-IFN.…”
Section: Modelling Ifn-based Therapymentioning
confidence: 99%
“…9,13,19 The relationship between drug concentration and antiviral effectiveness in blocking viral production can be described by an E-max model (Equation 3) εfalse(tfalse)=EmaxCfalse(tfalse)nEC50n+Cfalse(tfalse)n where C(t) is the drug concentration at time t ; EC 50 is the drug concentration needed to achieve an effectiveness of 50% of the maximum effect, E max ; and n is the Hill coefficient, a constant that determines the steepness of the drug concentration–effect curve. 22,31 Because drug concentrations are sometimes unavailable, empirical models have also been proposed to describe the patterns of change in drug effectiveness over time, 32,33 such as an exponential model for drugs whose concentrations decay or build up over time (Equation 4) εfalse(tfalse)=ε1+false(ε2ε1false)false(1ekεtfalse) where the treatment effectiveness starts from an initial level, ε 1 , changes to a final level, ε 2 , with k ε representing the rate of change of effectiveness. Therefore, if ε 2 is < ε 1 the model can mimic the effect of a decrease in drug effectiveness over time, as observed for example near the end of the dosing interval with weekly PEG-IFN.…”
Section: Modelling Ifn-based Therapymentioning
confidence: 99%
“…By extrapolation (Fig. 2C), we also determined the IIP 100 , defined as the IIP when D = 100 × IC 50 , to estimate the effects of high drug concentrations, because clinical doses can range between 10-and 100-fold above the IC 50 (19). We found that previous or current first-line drugs against HCV infection, such as IFN-α, TPV, SMV, and SOF, as well as CIs, can inhibit more than 99% of HCV replication in this concentration range (IIP 100 > 2).…”
Section: Resultsmentioning
confidence: 99%
“…In many instances, pharmacokinetic/pharmacodynamic properties may represent major determinants in the exploitability of certain compounds, rather than potency by itself [48]. Indeed a novel and currently pursued strategy is to provide long-acting formulations of antiretrovirals [49], as monthly or bi-monthly injections may provide a safer and more efficacious treatment option to oral dosage.…”
Section: Discussionmentioning
confidence: 99%